Performance evaluation of solar collectors using a solar simulator - Mohamed, Norhafana; Ismail, Ahmad Faris; Abdul Majid, Zafri Azran (IIUM Press, 2015)
Solar water heating systems is one of the applications of solar energy. One of the components of a solar water heating system is a solar collector that consists of an absorber. The performance of the solar water heating system depends on the absorber in the solar collector. In countries with unsuitable weather conditions, the indoor testing of solar collectors with the use of a solar simulator is preferred. Thus, this study is conducted to use a multilayered absorber in the solar collector of a solar water heating system as well as to evaluate the performance of the solar collector in terms of useful heat of the multilayered absorber using the multidirectional ability of a solar simulator at several values of solar radiation. It is operated at three variables of solar radiation of 400 W/m2, 550 W/m2 and 700 W/m2 and using three different positions of angles at 0º, 45º and 90º. The results show that the multilayer absorber in the solar collector is only able to best adapt at 45° of solar simulator with different values of radiation intensity. At this angle the maximum values of useful heat and temperature difference are achieved.